Challenge of Bovine Foot Skin Fibroblasts With Digital Dermatitis Treponemes Identifies Distinct Pathogenic Mechanisms - Newbrook, Kerry; Carter, Stuart D.; Crosby-Durrani, Hayley; Evans, Nicholas J. (Frontiers in Cellular and Infection Microbiology, 2021)
Bovine digital dermatitis (BDD) is a common infectious disease of digital skin in cattle and an important cause of lameness worldwide, with limited treatment options. It is of increasing global concern for both animal welfare and food security, imposing a large economic burden on cattle farming industries each year. A polytreponemal aetiology has been consistently identified, with three key phylogroups implicated globally: Treponema medium, Treponema phagedenis and Treponema pedis. Pathogenic mechanisms which might enable targeted treatment/therapeutic development are poorly defined. This study used RNA sequencing to determine global differential mRNA expression in primary bovine foot skin fibroblasts following challenge with three representative BDD treponemes and a commensal treponeme, Treponema ruminis. A pro-inflammatory response was elicited by the BDD treponemes, mediated through IL-8/IL-17 signalling. Unexpectedly, the three BDD treponemes elicited distinct mechanisms of pathogenesis. T. phagedenis and T. pedis increased abundance of mRNA transcripts associated with apoptosis, whilst T. medium and T. pedis increased transcripts involved in actin rearrangement and loss of cell adhesion, likely promoting tissue invasion. The upregulation of antimicrobial peptide precursor, DEFB123, by T. phagedenis spirochaetes may present a microbial ecological advantage to all treponemes within BDD infected tissue, explaining their dominance within lesions. A commensal, T. ruminis, significantly dysregulated over three times the number of host mRNA transcripts compared to BDD treponemes, implying BDD treponemes, akin to the syphilis pathogen (Treponema pallidum), have evolved as “stealth pathogens” which avoid triggering substantial host immune/inflammatory responses to enable persistence and tissue invasion. Immunohistochemistry demonstrated increased IL-6, IL-8, RND1 and CFB protein expression in BDD lesions, confirming in vitro fibroblast observations and highlighting the system’s value in modelling BDD pathogenesis. Several unique shared gene targets were identified, particularly RGS16, GRO1, MAFF and ZC3H12A. The three key BDD Treponema phylogroups elicited both distinct and shared pathogenic mechanisms in bovine foot skin; upregulating inflammation whilst simultaneously suppressing adaptive immunity. The novel gene targets identified here should enable future vaccine/therapeutic approaches.